The development and evaluation of a concussion education workshop for Gaelic games - Siobhán O’Connor; Cliona Devaney; Enda Whyte; Aoife Burke (PLoS ONE, 2025)
Concussions are frequent in Gaelic games and risky behaviours following a concussion are common. With the imminent integration of the Gaelic Athletic Association, Ladies Gaelic Football Association and Camogie Association, the development of a standardised concussion education initiative for all Gaelic games members is warranted. Thus, we aimed to develop a standardised concussion education workshop and evaluate if it improves concussion knowledge and attitudes in the Gaelic games community. A once-off concussion education workshop was developed in collaboration with the Gaelic games governing bodies and was delivered to 95 participants. Participants completed a survey (demographics, ROCKaS and the Perceptions of Concussion Inventory for Athletes [PCI-A]) pre-workshop and 1-month post-workshop (n = 55). Wilcoxon signed rank tests examined the differences pre- and 1-month post-workshop. One-month post-workshop, most participants strongly agreed/agreed that they can recognise concussion signs and symptoms (98.2%), know what to do in the event of a potential concussion (98.2%) and understand return to play guidelines (96.3%). Concussion knowledge (r = 0.34, p < 0.001), clarity (r = 0.45, p < 0.001) and control (r = 0.25, p = 0.01) significantly improved following the workshop. While concussion attitudes improved, the difference was not significant. No significant differences in anxiety, effects, treatment and symptom variability were noted from the PCI-A. A once-off time-efficient standardised concussion education workshop can enhance participants’ concussion knowledge, clarity of concussion and beliefs of how much control they have over the outcomes of a concussion. A national rollout of the standardised concussion education workshop across the Gaelic games community, implemented as part of a wider concussion initiative, is recommended.